Respostas
respondido por:
23
(x-r) + x + (x+r) = 6
3x = 6
x = 2
então
(2-r) . 2 . (2+r) = -10
8 -2r²= -10
R² = 9
R = + ou -3
Se for +3 = PA ( -1,2,5)
Se for -3 = PA (5,2,-1)
3x = 6
x = 2
então
(2-r) . 2 . (2+r) = -10
8 -2r²= -10
R² = 9
R = + ou -3
Se for +3 = PA ( -1,2,5)
Se for -3 = PA (5,2,-1)
Anônimo:
o ruim é que a questao nao fala se é crescente ou nao
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás